Implementasi Program Analisis Monitoring Berita Di Diskominfotik DKI Jakarta - Ali Sodikin; Dadang Akhmad Mulyadi (Syiar: Jurnal Komunikasi dan Penyiaran Islam, 2021)
The background of this research is the News Monitoring Analysis (AMB) program held by the DKI Jakarta Province Diskominfotik. This program is a new product at the DKI Jakarta Diskominfotik. Thus, the objectives of this study are: To analyze the implementation of the News Monitoring Analysis Program (AMB) in the management of print media news at the DKI Jakarta Information and Communications Communications and Statistics Agency (Diskominfotik) on Tuesday, September 1, 2020. The method used is a qualitative research method by observing News Monitoring Analysis Program (AMB) on managing print media news. The analytical method used is descriptive qualitative method. The data used are primary and secondary data. The primary data collection method is by conducting interviews. The results of this study indicate that the implementation of the News Monitoring Analysis (AMB) program in the management of print media news starts from the process of news gathering, news selection, news processing and news analysis. Print media news collected in the AMB Program has been digitized apart from being a website. Thus, the suggestion from the results of this study is that DKI Jakarta Diskominfotik represented from the AMB Program develops an application in the Google Playstore and Apple App Store, so that print media news in the AMB program can be more easily accessed with news information with the appropriate display on mobile phones.